Effect of nintedanib in patients with systemic sclerosis-associated interstitial lung disease and risk factors for rapid progression - Toby M Maher; Michael Kreuter; Vanessa Smith; Yannick Allanore; Elizabeth R Volkmann; Dinesh Khanna; Christopher P Denton; Anna-Maria Hoffmann-Vold; Shervin Assassi; Masataka Kuwana; Margarida Alves; Christian Stock; et al. (RMD Open, 2023)
Objective To investigate the rate of decline in forced vital capacity (FVC), and the effect of nintedanib on the rate of decline in FVC, in subjects with systemic sclerosis-associated interstitial lung disease (SSc-ILD) who had risk factors for rapid decline in FVC.Methods The SENSCIS trial enrolled subjects with SSc and fibrotic ILD of ≥10% extent on high-resolution CT. The rate of decline in FVC over 52 weeks was analysed in all subjects and in those with early SSc (<18 months since first non-Raynaud symptom), elevated inflammatory markers (C reactive protein ≥6 mg/L and/or platelets ≥330×109/L) or significant skin fibrosis (modified Rodnan skin score (mRSS) 15–40 or mRSS ≥18) at baseline.Results In the placebo group, the rate of decline in FVC was numerically greater in subjects with <18 months since first non-Raynaud symptom (−167.8 mL/year), elevated inflammatory markers (−100.7 mL/year), mRSS 15–40 (−121.7 mL/year) or mRSS ≥18 (−131.7 mL/year) than in all subjects (−93.3 mL/year). Nintedanib reduced the rate of FVC decline across subgroups, with a numerically greater effect in patients with these risk factors for rapid FVC decline.Conclusion In the SENSCIS trial, subjects with SSc-ILD who had early SSc, elevated inflammatory markers or extensive skin fibrosis had a more rapid decline in FVC over 52 weeks than the overall trial population. Nintedanib had a numerically greater effect in patients with these risk factors for rapid ILD progression.